The nuclear pore protein NUP98 impedes LTR-driven basal gene expression of HIV-1, viral propagation, and infectivity - Chintala, Kumaraswami; Yandrapally, Sriram; Faiz, Warisha; Kispotta, Chhaya Rani; Sarkar, Satarupa; Mishra, Krishnaveni; Banerjee, Sharmistha (Frontiers in Immunology, 2024)
Nucleoporins (NUPs) are cellular effectors of HIV-1 replication that support nucleocytoplasmic trafficking of viral components. However, these also non-canonically function as positive effectors, promoting proviral DNA integration into the host genome and viral gene transcription, or as negative effectors by associating with HIV-1 restriction factors, such as MX2, inhibiting the replication of HIV-1. Here, we investigated the regulatory role of NUP98 on HIV-1 as we observed lowering of its endogenous levels upon HIV-1 infection in CD4+ T cells. Using complementary experiments in NUP98-overexpression and knockdown backgrounds, we deciphered that NUP98 negatively affected HIV-1 LTR promoter activity and lowered released virus levels. The negative effect on promoter activity was independent of HIV-1 Tat, suggesting that NUP98 prevents the basal viral gene expression. ChIP-qPCR showed that NUP98 associated with HIV-1 LTR, with the negative regulatory element (NRE) of HIV-1 LTR playing a dominant role in NUP98-mediated lowering of viral gene transcription. Truncated mutants of NUP98 showed that the attenuation of HIV-1 LTR-driven transcription is majorly contributed by its N-terminal region. Interestingly, the virus generated from the producer cells transiently expressing NUP98 showed lower infectivity, while the virus generated from NUP98 knockdown CD4+ T cells, showed higher infectivity as assayed in TZM-bl cells, corroborating anti-HIV-1 properties of NUP98. Collectively, we show a new non-canonical function of a nucleoporin adding to the list of moonlighting host factors regulating viral infections. Downregulation of NUP98 in a host cell upon HIV-1 infection supports the concepts of evolutionary conflicts between viruses and host anti-viral factors.